The Snow White effect: How food colour saturation impacts food likeability - Jerónimo, R.; Rocha, M. L.; Simão, C. (5th Symposium on Ethics and Social Responsibility Research, 2019)
In our daily lives we are constantly in contact with chromatic stimuli, either by the objects we see or by everything that nature has been busy painting, such as food. Our first contact with food is through our eyes, therefore, it makes colour an important indicator for food assessment and selection. This research aimed to study how a specific colour attribute - the saturation – of plant origin (vegetables and fruits) and animal food products, both natural and confectioned, has an influence on their likeability. For this, 32 images of edible and inedible (objects) products were taken from the Food-Pics database, of the subset already validated for the Portuguese population. For each image, a high and low saturation version was created. Both versions of the 32 images were randomly presented to 48 participants who, using a scale, reported their likeability for the products’ shown. The results reported that colour saturation of foods, but not of objects, significantly affects the likeability for the products. A greater likeability is found for both plant and animal origin foods that present a higher level of colour saturation, irrespectively of being natural or confectioned products. These findings have major implications for the promotion of healthy and environmentallyfriendly food consumption. This can be accomplished by promoting the use of more saturated colours in the communication of organic fruits and vegetables, whereas, animal products should be presented with low colour saturation. With this, we can appeal for consumer responsibility by encouraging healthier eating habits and behaviours supporting a more sustainable food production system, aiming for a more sustainable world.